2021
DOI: 10.1111/acel.13465
|View full text |Cite
|
Sign up to set email alerts
|

YAP prevents premature senescence of astrocytes and cognitive decline of Alzheimer's disease through regulating CDK6 signaling

Abstract: Senescent astrocytes accumulate with aging and contribute to brain dysfunction and diseases such as Alzheimer's disease (AD), however, the mechanisms underlying the senescence of astrocytes during aging remain unclear. In the present study, we found that Yes‐associated Protein (YAP) was downregulated and inactivated in hippocampal astrocytes of aging mice and AD model mice, as well as in D‐galactose and paraquat‐induced senescent astrocytes, in a Hippo pathway‐dependent manner. Conditional knockout of YAP in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 63 publications
0
34
0
Order By: Relevance
“…Selectively knockout YAP in astrocytes promotes premature senescence of astrocytes, which further confirmed the senescence-inhibiting effects of YAP in astrocytes [ 6 ]. Cyclin-dependent kinase 6 (CDK6), as a downstream molecule of YAP, is decreased in YAP -/- astrocytes in vivo and in vitro , and over-expression of CDK6 partially rejuvenates YAP -/- astrocytes, indicating that YAP inhibits astrocytic senescence through the CDK6 signaling [ 6 ]. Moreover, activation of YAP by XMU-MP-1 (an inhibitor of Hippo kinase MST1/2) improves the cognitive decline of AD model mice [ 6 ].…”
mentioning
confidence: 66%
See 2 more Smart Citations
“…Selectively knockout YAP in astrocytes promotes premature senescence of astrocytes, which further confirmed the senescence-inhibiting effects of YAP in astrocytes [ 6 ]. Cyclin-dependent kinase 6 (CDK6), as a downstream molecule of YAP, is decreased in YAP -/- astrocytes in vivo and in vitro , and over-expression of CDK6 partially rejuvenates YAP -/- astrocytes, indicating that YAP inhibits astrocytic senescence through the CDK6 signaling [ 6 ]. Moreover, activation of YAP by XMU-MP-1 (an inhibitor of Hippo kinase MST1/2) improves the cognitive decline of AD model mice [ 6 ].…”
mentioning
confidence: 66%
“…YAP is down-regulated in D-galactose-induced senescent glioblastoma cells, and over-expression of YAP partially reverses the senescence of glioblastoma cells, indicating a role of YAP in cellular senescence [ 5 ]. Recently, we have found that YAP is down-regulated and inactivated in senescent astrocytes, not only in cultured senescent astrocytes, but also in hippocampal astrocytes of the aging mice and AD model mice, in a Hippo pathway-dependent manner, indicating a role of YAP in astrocytic senescence [ 6 ]. Selectively knockout YAP in astrocytes promotes premature senescence of astrocytes, which further confirmed the senescence-inhibiting effects of YAP in astrocytes [ 6 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…YAP upregulates the expression of PLAU [ 39 ], and YAP promotes senescence in both endothelial cells and smooth muscle cells [ 40 ], suggesting that PLAU may serve as a downstream molecule, contributing to YAP-induced vascular cell senescence. However, in another study on glioma cells, glioblastoma cells, and astrocytes, it was shown that YAP prevents senescence induced by several factors [ 41 , 42 ], and in cancer cells, PLAU accelerates proliferation [ 39 , 43 , 44 , 45 ]. These indicate that the involvement of PLAU in cellular senescence is conditional and likely cell-type dependent.…”
Section: Discussionmentioning
confidence: 99%
“…It prevented gliosis, decreased NFTs deposition and degeneration of neurons, and helped to preserve cognitive functions. Xu et al (2021) reported downregulation of the Yes-associated protein (YAP) paralleled with a decrease of lamin B1 in hippocampal astrocytes during normal ageing and in APP/PS1 mice. The downregulation of YAP was also shown in D-galactose and paraquat-induced senescent astrocytes.…”
Section: The Impact Of Ageing On the Responses And Phenotypes Of Astr...mentioning
confidence: 98%